Use Of An Automated Temperature Data Logger (ATDL) During Falling Weight Deflectometer (FWD) Testing - Korczak, R; Tighe, S; Cimini, G (Transportation Association of Canada, 2012)
There are various methods of designing an overlay for a flexible pavement. A common method presently used involves analyzing FWD data to assess the structural capacity of a pavement section and using the backcalculated data to determine the overlay thickness. Deflection results of all pavements are dependent on seasonal variations that affect the underlying aggregate and subgrade. The results from asphalt pavements are also dependent on the temperature of the asphalt. In order to meaningfully analyze the deflections or the deflection results, the deflection analysis results, must be adjusted to account for seasonal and temperature effects. A piece of equipment that has recently been introduced into the Long Term Pavement Performance (LTPP) program is the Automated Temperature Data Logger (ATDL). The ATDL is designed to provide continuous automated data collection for pavement temperature gradient measurements associated with FWD deflection tests on LTPP test sections. This report will examine the effect of using different sources of temperature gradient data and temperature models used to adjust FWD deflection results on overlay design for pavement sections in the LTPP program. All data will be sourced from the LTPP database and will use data from various states in the North Atlantic and North Central regions of North America. Furthermore, this report will discuss the impacts of the findings on pavement management and sustainability.